Developing Outcome Measures for Criminal Justice Information Sharing: A Study of a Multi-Jurisdictional Officer Notification System for Policing Sex Offenders in Southern California - Kovalchik, Stephanie A. (American journal of criminal justice, 2017)
Information-sharing efforts are broadly assumed by criminal justice and security practitioners to be effective, yet their impact on policing performance has not been thoroughly studied. This paper develops measures for an information-sharing system in a population of sex offenders in Southern California. We compared interagency involvement and policing outcomes for registered sex offenders with (n = 3,919) and without (n = 581) records pertaining to their sex offender status in the Officer Notification System (ONS) of ARJIS. To account for differences in criminal activity, offenders were matched on each of four focal incidents (citations, field interviews, crime cases, and arrests) and compared on outcomes that followed the focal incident. Compared to controls, sex offenders with ONS records were 75 % more likely to be involved with multiple agencies, 92 % more likely to have a citation following a crime case, 34 % more likely to have multiple crime cases (i.e., a crime case following an initial crime case), 44 % more likely to have a field interview following a citation, over 2 times more likely to have a field interview following a crime case, and 20-30 % more likely to have an arrest after a crime case, citation, or field interview. Novel measures of information sharing revealed links between the sharing of information about sex offender registrant status and the frequency and timing of police incidents and inter-agency involvement.